2021
DOI: 10.3390/plants10102032
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of the Leaves of Diospyros kaki (Persimmon)

Abstract: Diospyros kaki (persimmon) leaves have long been utilized as traditional medicine for the treatment of ischemic stroke, angina, and hypertension and as a healthy beverage and cosmetic for anti-aging. This study aimed to isolate as many compounds as possible from an ethanol extract of the persimmon leaves to identify the biologically active compounds. The antioxidative effect of the ethyl acetate layer from the ethanol extract of the persimmon leaves was demonstrated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…For instance, Fan and He [ 46 ] developed an HPLC method to identify triterpene acids from PL, and the compounds were rotungenic acid, 24-hydroxyursolic acid, and barbinervic acid and its epimer. Similar to this study, seven triterpenoids were isolated from the Korean PL, namely barbinervic acid, diospyric acid B, pomolic acid, rotungenic acid, oleanolic acid, siaresinolic acid, and ursolic acid [ 16 ]. Moreover, Chen et al [ 47 ] reported five triterpenoids such as ursolic acid, α-amyrin, uvaol, 19 α,24-dihydroxyursolic acid, and 19α-hydroxy ursolic acid in PL.…”
Section: Bioactive Compounds Of Plmentioning
confidence: 75%
See 3 more Smart Citations
“…For instance, Fan and He [ 46 ] developed an HPLC method to identify triterpene acids from PL, and the compounds were rotungenic acid, 24-hydroxyursolic acid, and barbinervic acid and its epimer. Similar to this study, seven triterpenoids were isolated from the Korean PL, namely barbinervic acid, diospyric acid B, pomolic acid, rotungenic acid, oleanolic acid, siaresinolic acid, and ursolic acid [ 16 ]. Moreover, Chen et al [ 47 ] reported five triterpenoids such as ursolic acid, α-amyrin, uvaol, 19 α,24-dihydroxyursolic acid, and 19α-hydroxy ursolic acid in PL.…”
Section: Bioactive Compounds Of Plmentioning
confidence: 75%
“…The major compounds of PL are flavonoids, tannins, vitamins, and terpenoids. PL have long been considered a traditional medicine to treat ischemic angina, stroke, internal hemorrhage, hypertension, atherosclerosis, and infectious diseases, as well as paralysis, frostbite, burns, and constipation, which have been mentioned in ancient Chinese medical books [ 10 , 16 ]. In particular, NXQ is a protected drug of Traditional Chinese Medicine and is used in managing cardio- and cerebrovascular diseases [ 5 ].…”
Section: Traditional Uses and Industrial Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…The extract of Japanese persimmon has been shown to have antioxidant properties [ 15 , 16 ]. Various Phytochemicals such as flavonoids, diospyric acid, scopoletin, quercetin, kaempferol, oleanolic acids tannins, catechin, anthocyanidin, etc have been reported from different parts of D. Kaki [ 17 ]. These isolated phytochemicals have been reported for excellent antioxidant potential [ 7 , 18 ].…”
Section: Introductionmentioning
confidence: 99%